A Spatial Analysis of Atmospheric Ammonia and Ammonium in the U.K. - M.A. Sutton; Y.S. Tang; U. Dragosits; N. Fournier; A.J. Dore; R.I. Smith; K. J. Weston; D. Fowler (The Scientific World Journal)
As measures are implemented internationally to reduce SO2 and NOx emissions, attention is falling on the contribution of NH3 emissions to acidification, nitrogen eutrophication, and aerosol formation. In the U.K., a monitoring network has been established to measure the spatial distribution and long-term trends in atmospheric gaseous NH3 and aerosol NH4+. At the same time, an atmospheric chemistry and transport model, FRAME, has been developed with a focus on reduced nitrogen (NHx). The monitoring data are important to evaluate the model, while the model is essential for a more detailed spatial assessment. The national network is established with over 80 sampling locations. Measurements of NH3 and NH4+ (at up to 50 sites) have been made using a new low-cost denuder-filterpack system. Additionally, improved passive sampling methods for NH3 have been applied to explore local variability. The measurements confirm the high spatial variability of NH3 (annual means 0.06 to 11 mg NH3 m3), consistent with its nature as a primary pollutant emitted from ground-level sources, while NH4+, being a slowly formed secondary product, shows much less spatial variability (0.14 to 2.4 mg NH4+ m3). These features are reproduced in the FRAME model, which provides estimates at a 5-km level. Analysis of the underlying NH3 emission inventory shows that sheep emissions may have been underestimated and nonagricultural sources overestimated relative to emissions from cattle. The combination of model and measurements is applied to estimate spatial patterns of dry deposition to different vegetation types. The combined approach provides the basis to assess NHx responses across the U.K. to international emission controls.